2004
DOI: 10.1159/000080460
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin Levels in Marasmic Children and the Relationship between Leptin and Lipid Profile

Abstract: Background and Aims: Leptin and dyslipidemia are risk factors for cardiovascular disease. We measured leptin and lipid levels, and examined whether there is an effect of leptin on lipid profile in marasmic children. Methods: Fifty children (25 marasmic, 25 healthy) aged between 0.3 and 2.5 years were evaluated. Leptin levels were compared with lipid profile in marasmic and healthy children. The relationships between leptin and sex, body mass index and lipid profile were investigated in marasmic children. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Serum lipid profiles were studied in malnourished children previously, and similar to our study total cholesterol levels were found to be low in malnourished children compared to healthy controls in all studies [18192021]. Additionally, they also found that low-density lipoprotein and high-density lipoprotein levels were low and triglyceride levels were high in malnourished children.…”
Section: Discussionsupporting
confidence: 85%
“…Serum lipid profiles were studied in malnourished children previously, and similar to our study total cholesterol levels were found to be low in malnourished children compared to healthy controls in all studies [18192021]. Additionally, they also found that low-density lipoprotein and high-density lipoprotein levels were low and triglyceride levels were high in malnourished children.…”
Section: Discussionsupporting
confidence: 85%
“…However, in that study, children with marasmus who were 12‐27 months of age had high cholesterol and triglyceride levels for age (149 ± 13 mg/dL and 171 ± 17 mg/dL, respectively). Other authors showed that the blood lipids in marasmic children can be normal 12 or elevated, especially triglycerides, 15 associating this finding with a defect in removal of blood triglycerides in consequence of reduced LPL activity 16…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that leptin correlates with the individual's body weight, fat mass and BMI but like the IGF axis it is affected by extremes in energy intake such as fasting and overfeeding 12 , 14 . Leptin levels have been found to be low in many forms of malnutrition, including intra-uterine growth retardation and malnourishment 15 , 16 . Thus leptin levels were analysed in this group of children.…”
mentioning
confidence: 99%